Tradizione, identità nazionale, etnosimbolismo e discriminazione in Ungheria: sfidare i diritti fondamentali con le loro stesse “armi” (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO. 1. Introduzione - 2. Sfera privata, narrative politiche e diritto: famiglia e nazione nel Programma di cooperazione nazionale e nella nuova Costituzione ungherese - 3. La discriminazione delle minoranze: il divieto di registrazione del cambiamento di genere adottato durante la pandemia da COVID-19 - 4. Spazio pubblico, tradizione, identità nazionale e radici cristiane - 5. Etnosimbolismo e malessere sociale tra rifiuto del linguaggio politico centrato sui diritti fondamentali e sfruttamento delle aspettative che questi ingenerano - 6. Conclusioni.Tradition, National Identity, Ethnosymbolism and Discrimination in Hungary: Challenging Fundamental Rights with their Own WeaponsAbstract: The ruling coalition in Hungary values tradition, retrieving it in areas that affect both the private sphere of citizens and the public sphere of institutions through political narratives that are implemented by law. Although the "recovered" and interpreted tradition shapes a collective imagination and a normative framework that, according to current language, could be described as extremely conservative, political narratives and normative interventions contribute to social change in an illiberal sense. They intercept widespread malaise and increase discrimination against minorities already at risk. Moving from a unique model of social regulation based on the family, the ruling coalition establishes a link between the latter and the nation, introduces bans on the registration of gender change and the promotion of LGBT contents. Within migration policy, it also constructs the target of migrants and uses Christianity as an ethno-identity component, meanwhile adopting measures that prevent the implementation of Christian values. Moreover, Hungarian narratives, while rejecting the fundamental rights-centered narrative of the liberal tradition, are able to politically "exploit" the expectations it creates among citizens. Following a populist logic, the ruling coalition openly rejects the liberal fundamental rights narrative, but at the same time fully utilizes it.